THE FEATURES OF FORMING OF THE PATHOLOGY OF PERIODONTAL TISSUES IN CHILDREN LIVING IN ECOLOGICALLY UNFAVORABLE TERRITORY - N.V. Malko; E.V. Bezvushko (Ukrainian Medical Stomatological Academy, 2015)
The last year of studies indicate on the high prevalence of main dental diseases in children from ecologically unfavorable regions. Periodontal diseases take the second place by frequency and prevalence after caries, therefore is the significant problem of the pediatric dentistry. The purpose of the study is evaluation of the state of periodontal tissues in children living in the conditions of complex influence of the anthropogenic loading and natural geochemical conditions. Materials and research methods. With the purpose to evaluate the state of periodontal tissues the epidemiology examination of 642 children that live on territory with the high level of contamination and natural deficit of iodine and fluorine (Yavoriv and Zhydachiv) was conducted. For the control data 214 children, residents of Lviv, that is characterized as conditionally "clean region", were examined. The 7, 12 and 15 years-old children were examined in this research. The state of periodontal tissues was assessed on the results of questioning, review of the oral cavity and use of the periodontal indices and tests (index of PMA, the test of Schiller-Pisarev). Statistical processing of the materials is worked out on the computer in program Excel. Results of the research and their discussion. The analysis of epidemiological data showed that the prevalence of periodontal diseases in examined children from region with increased anthropogenic loading and low content of iodine and fluorine (ЕPR) presented 66,98 ± 1,85 % in average, that is significantly higher in relation to children who live in Lviv - 46,26 ± 3,40 %, р<0,01. The prevalence of periodontal diseases in children from EPR, by the criteria of WHO, corresponds to a high level, while in children of the comparison group characterized as medium. In the result of analysis revealed that in children of Yavoriv the mean value of the prevalence of periodontal diseases was higher than among residents of the city of Zhydachiv (71,86 ± 2,46 % against 61,68 ± 2,77 %, р<0,05). It is necessary to notice that among the examined children of both settlements, with age the morbidity grew, but in children of Yavoriv, in all age groups the increase of values took place more intensive. So, the prevalence of periodontal disease in the 7-years-old residents of Yavoriv presents 66,08 ± 4,41 %, р<0,05 and gradually growing, at the age of 12 years, the morbidity of periodontal tissues was revealed in 74,0 ± 4,38 % examined, р>0,05. The maximal values of the prevalence of inflammatory diseases of periodontal tissues were diagnosed in the 15-years-old children of Yavoriv - 75,63 ± 3,93 %, р>0,05. At the analysis of morbidity of periodontal tissues among children of Zhydachiv, was found that the prevalence of disease in the 7-years-old children presented in 47,82 ± 5,21 % and increased to 62,62 ± 4,67 % in children at the age 12 years. The highest values of morbidity of periodontal tissues (72,47 ± 4,27 %, р<0,05) determined in the 15-years-old adolescents of Zhydachiv. The attention pays the prevalence of diseases of periodontal tissues, by the criteria of WHO, in children of Yavoriv in all age groups, which is corresponded to a high level, while the medium level of morbidity in the 7-years-old children of Zhydachiv was identified, and the morbidity of periodontal tissues in the 12-15 year-old examined was characterized as high. Conclusions. The prevalence of periodontal diseases in children living in polluted areas, was in 1.4 times higher than in children from ecologically clean region, that expressed as increase of percentage of children with chronic and bertrice gingivitis. The prevalence of periodontal disease was increased with age in both study groups, but in children living in unfavorable environmental conditions, it was observed a higher prevalence of periodontal tissues.